2016
DOI: 10.17265/2161-6221/2016.9-10.003
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Structured Cu/W Brazing Fillers for Advanced Joining Applications

Abstract: Nano-multilayered brazing fillers offer a high potential for joining heat sensitive materials at reduced temperatures. In the current work Cu/W based nano-multilayered coatings, fabricated via physical vapor deposition (PVD) are studied. Joints were successfully produced via deformation dilatometry at temperature of 750 ºC and a mechanism for the bonding process is suggested. The promising results indicate an attractive pathway for using the versatile ability of PVD to precisely control the microstructure on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Our research team envisages another class of nanostructured filler materials, namely, hybrid nanolaminates, for selective bonding at reduced temperatures, which may tackle some of the aforementioned limitations of emerging nano-joining methods. ,, The nanolaminates (also referred to as nanomultilayers; NMLs) are composed of a stack of alternating nanolayers (NLs) of a metal or an alloy ( here : eutectic Ag–Cu 40at.% ) and a chemically inert barrier material (a nitride, oxide, or refractory metal; here AlN). Such hybrid NML systems can be easily produced as a coating or as a foil by (reactive) magnetron sputtering with accurate control of the NL thickness, modulation periodicity, chemical composition, in-plane texture, and growth stress ,,, Figure a,b show cross-sectional and planar scanning electron microscopy (SEM) micrographs of the type of hybrid nanolaminate addressed in the present study, which is composed of alternating NLs of an Ag–Cu 40at.% alloy and an AlN barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Our research team envisages another class of nanostructured filler materials, namely, hybrid nanolaminates, for selective bonding at reduced temperatures, which may tackle some of the aforementioned limitations of emerging nano-joining methods. ,, The nanolaminates (also referred to as nanomultilayers; NMLs) are composed of a stack of alternating nanolayers (NLs) of a metal or an alloy ( here : eutectic Ag–Cu 40at.% ) and a chemically inert barrier material (a nitride, oxide, or refractory metal; here AlN). Such hybrid NML systems can be easily produced as a coating or as a foil by (reactive) magnetron sputtering with accurate control of the NL thickness, modulation periodicity, chemical composition, in-plane texture, and growth stress ,,, Figure a,b show cross-sectional and planar scanning electron microscopy (SEM) micrographs of the type of hybrid nanolaminate addressed in the present study, which is composed of alternating NLs of an Ag–Cu 40at.% alloy and an AlN barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, such size-dependent materials stabilities are known to be vital to the high performance and long-term service of a wide range of nanotechnologies. On one hand, the intrinsically higher mobility of electrons (holes) and/or ions (ion vacancies) in the metastable nanostructured systems can be exploited for high performance electronic devices and device integration at lower temperatures. , On the other hand, stable thin films and multilayered microstructures can be utilized to achieve smooth optical/electrical response and extended device lifetimes. , A fundamental understanding and engineering know-how of mass transport phenomena in metal/ceramic thin films and NMLs is needed to adjust their optical performances and electrical conductivities for photonics or electronics applications.…”
Section: Introductionmentioning
confidence: 99%
“…A more extensively studied system is the Cu/W NML, where W serves as the diffusion barrier between the Cu layers. With the use of this multilayer, the formation of a joint similar to the mechanism of a diffusion bonding was observed at 750°C [28]. The study of its thermal behaviour revealed the degradation of the multilayer structure, transforming into a spheroidised nanocomposite at 700°C [29].…”
Section: Introductionmentioning
confidence: 86%